Mechanosignals in abdominal aortic aneurysms - Lowis, Christiana; Ramara Winaya, Aurellia; Kumari, Puja; Rivera, Cristobal F.; Vlahos, John; Hermantara, Rio; Pratama, Muhammad Yogi; Ramkhelawon, Bhama (Frontiers in Cardiovascular Medicine, 2023)
Cumulative evidence has shown that mechanical and frictional forces exert distinct effects in the multi-cellular aortic layers and play a significant role in the development of abdominal aortic aneurysms (AAA). These mechanical cues collectively trigger signaling cascades relying on mechanosensory cellular hubs that regulate vascular remodeling programs leading to the exaggerated degradation of the extracellular matrix (ECM), culminating in lethal aortic rupture. In this review, we provide an update and summarize the current understanding of the mechanotransduction networks in different cell types during AAA development. We focus on different mechanosensors and stressors that accumulate in the AAA sac and the mechanotransduction cascades that contribute to inflammation, oxidative stress, remodeling, and ECM degradation. We provide perspectives on manipulating this mechano-machinery as a new direction for future research in AAA.